Dietary risk assessment for pesticide residues among farmland communities in the selected municipalities of Bukidnon, the Philippines - RJ Krista Raye Y. Leocadio; Beth A. Polidoro; Thomas M. Cahill; Maria Kristina O. Paler (CyTA - Journal of Food)
The growing population in the Philippines pressures its agriculture sector, leading farmers to use pesticides to boost crop productivity. However, this results in pesticide residues on produce, posing potential health risks. This study assessed pesticide levels in fruits and vegetables from selected farms in Bukidnon using Gas Chromatography-Mass Spectroscopy. All 67 samples tested positive, with 10 out of 14 target pesticides detected. Eggplant, broccoli, and bittergourd had the highest residue levels (60%), while chayote and string beans had the least (10%). Most samples were within maximum residue limits (MRLs), except broccoli and cabbage, which exceeded the MRL for indoxacarb. Dietary risk assessment of 410 consumers showed exposure levels below the U.S. EPA’s reference dose, suggesting no immediate noncancer health effects. However, lifetime exposure to multiple pesticides remains a concern. Consumers should be educated on proper handling, storage, and consumption practices to minimize pesticide-related health risks.